Public–private partnerships improve health outcomes in individuals with early stage Alzheimer’s disease - Galvin JE (Dove Medical Press, 2014)
James E Galvin,1 Magdalena I Tolea,1 Nika George,2 Cheryl Wingbermuehle31Alzheimer Disease Center, Departments of Neurology, Psychiatry and Population Health, New York University Langone Medical Center, New York, NY, USA; 2Clinical Psychology Program, University of Missouri – St Louis, 3Alzheimer’s Association, St Louis Chapter, St Louis, MO, USAPurpose: In a collaborative effort between the Missouri Department of Health, Area Agencies on Aging (AAA), Alzheimer Association, and academic researchers, we tested whether early dementia detection and comprehensive care consultations would improve health outcomes in care receivers (CRs) and their family caregivers (FCGs), therefore addressing an important public health concern.Participants and methods: A total of 244 community-dwelling older adults screened for early-stage dementia by the AAA field staff were referred to the Alzheimer Association and participated in Project Learn MORE (Missouri Outreach and Referral Expanded) (PLM) – a 2-year, nonrandomized multisite intervention consisting of comprehensive care consultations to improve coping skills. PLM participants were compared against 96 controls receiving the Alzheimer Association’s “usual services” between January 2011 and December 2012. We examined CR and FCG outcomes, including burden, care confidence, and mood, as effects of PLM, on delaying transitions in level of care.Results: CRs showed improved knowledge (P=0.002) and reduced depression (P=0.007), while FCGs demonstrated improved knowledge (P=0.003) and ability to identify sources of support for the CR (P=0.032) and for themselves (P=0.043). However, FCGs were more burdened after PLM (P=0.02), due to increased awareness of Alzheimer’s disease. PLM delayed transitions in care (odds ratio [OR] 3.32, 95% confidence level [CI]: 1.25–8.83) with the number needed to treat =6.82.Conclusion: PLM was successful in improving detection of incident cases of dementia in the community and in connecting patients and their families with needed services. Our findings support the use of state agencies and community service partners to detect dementia. Early implementation of psychosocial interventions could have significant impact in improving patient- and family-centered outcomes, potentially providing a cost-efficient alternative to pharmacotherapy.Keywords: dementia screening, AD8, social support, caregiver burden, transition in care